The Islamic Values and Democratic Ideals Navigating the Intersection of Islam and Democracy - Ahmad Nabilul Maram; M. Ridlwan Nasir; Husein Aziz (Jurnal Keislaman, 2023)
The debate about democracy and Islam has consistently been juxtaposed as if it never reaches a final resolution, leading to disharmony between pro and con camps in relation to democracy, especially in the contemporary era. This study elucidates that there is no need for a dichotomy between democracy and the discourse of the Quran, as the Quranic vision is not contradictory to the spirit of democracy. This research is conducted based on direct observation, taking into account empirical evidence from literature and phenomena occurring within society. The study concludes that such debate is not of paramount importance; rather, what is more urgent is fostering public participation capable of implementing democracy that aligns with the vision of the Quran and Islam at large, to prevent all forms of injustice, authoritarianism, intolerance, and oppression.